INFLUENCE OF EXPERIENTIAL VALUE ON BRAND IMAGE AND CUSTOMER LOYALTY OF VISTA CONCRETE TILES PT. YASKA POST OF THE EARTHQUAKE DISASTER IN THE CITY OF MATARAM - Saddam Husein; Akhmad Saufi; Baiq Handayani Rinuastuti (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2023)
This study aims to find out the effect of Experiential Value on Brand image and customer loyalty at PT. Yaska after the earthquake in the city of Mataram using the associative quantitative method with a sample of 40 respondents and using a questionnaire as a tool for collecting data whose results were analyzed using smart PLS through the inner and outer model tests. The results of this study show significant positive results where the Experiential Value on Brand image and customer loyalty where the more positive the Experiential Value received by customers, the better the Brand image of a brand and increase customer loyalty. Keywords: Experiential Value, Brand Image, Customer Loyalty, Concrete Tiles